Reasonableness in capacity law - Hass, B (Wiley, 2023)
It is not uncommon for people to hold bizarre views. Sometimes, these views appear before the courts in mental capacity cases. Judges must then decide if the views are so bizarre that they constitute evidence of incapacity or, instead, if those views are the everyday sort that do not constitute such evidence. The idea behind the distinction is that the everyday sort can be false but, in some important sense, not that unreasonable. But what should tip the balance of reasons for a view to count as severely unreasonable rather than merely so? It turns out that capacity law is unable to provide a principled answer to this question because it lacks a standard to parse beliefs. This paper offers such a standard, focussing on the ability to reason, or the ‘use and weigh’ criterion, which features in most capacity statutes. The standard takes the form of a threshold with four necessary conditions. The main idea is that when a person's belief satisfies those conditions, it counts as evidence of an inability to reason. The standard's objective is to displace the various unarticulated conceptions of reasonableness which judges are currently compelled to use to determine questions of reasoning ability.